Laser welding introduced segregation and its influence on the corrosion behaviour of Al-Cu-Li alloy. (1st May 2018) - Zhang, Xinxin; Liu, Bing; Zhou, Xiaorong; Wang, Junjie; Hashimoto, Teruo; Luo, Chen; Sun, Zhihua; Tang, Zhihui; Lu, Feng
Highlights: 2A97-T3 Al-Cu-Li alloy is sensitized by laser beam welding. The sensitization is due to segregation and formation of interdendritic intermetallics. The equiaxed dendrite zone is most susceptible to corrosion. Abstract: In the present study, the microstructure and corrosion behaviour of laser beam welded 2A97 alloy are investigated. Welding process results in segregation of alloying elements within the fusion zone and, consequently, formation of T1 (Al2 CuLi), TB (Al7 Cu4 Li) and R (Al5 CuLi3 ) phase interdendritic intermetallics. The distribution of the interdendritic intermetallics is non-uniform across the weld. In NaCl solution, corrosion initiates at interdendritic intermetallic with selective dissolution of Al and Li, resulting in a copper-rich remnant, which subsequently acts as effective cathode supporting the dissolution of alloy matrix. The equiaxed dendrite zone at the centre of the weld is most susceptible to corrosion.